Serum levels of antimicrobial peptides (Cathelicidins and Beta Defensins-1) in patients with periodontitis - Al-Daragi , Fatima Z; Al-Ghurabi , Batool H; Abdullah, Nik Nairan (Journal of Baghdad College of Dentistry, 2024)
Background: periodontitis is a multifactorial oral inflammatory disease characterized by the gradual loss of bone and eventual tooth loss. It starts with microbes and is then influenced by the environment. A diverse family of host defense major compounds known as antimicrobial peptides react quickly to combat microbial invasion and challenge. These little cationic peptides are crucial for the development of innate immunity. The goal of this study was to evaluate the blood levels of healthy individuals and patients with periodontitis for cathelicidins and human beta-defensin-1. In this case-control study, 35 healthy volunteers (matched exactly by age and sex to the patients) and 50 periodontitis patients (aged 20 to 59) participated. In this investigation, periodontal parameters such as plaque index, gingival index bleeding on probing, probing pocket depth, and clinical attachment loss were employed. The levels of cathelicidins and human beta-defensin-1 in patients and controls were estimated using ELISA after blood samples from all individuals were taken. The current findings showed that the mean levels of cathelicidin and human beta defensin-1 were significantly higher (P˂0.01) in the patient group compared to the control group, and that there was no significant correlation with all clinical periodontal parameters. These findings support the notion that antimicrobial peptides play a crucial role in periodontitis' inflammatory process.